MMP-9 as a marker for the association between childhood/adolescent trauma and psychosis - Lisbôa, João Roberto Fernandes (2024)
Psychotic disorders are thought to involve a complex interaction between biological and environmental factors. Matrix metalloproteinase-9 (MMP-9) has been implicated in the pathophysiology of psychosis through mechanisms such as the dysfunction of parvalbumincontaining GABAergic interneurons and synaptic dysfunction. Recent evidence regarding the detrimental role of early stress in neurodevelopment and its modulation of MMP-9 activity emphasizes the need to understand the relationship between childhood/adolescent trauma and MMP-9 in psychosis. This study aims to investigate plasma MMP-9 activity in individuals with first-episode psychosis (FEP), non-affected siblings, and community-based controls to determine how childhood/adolescent trauma might influence MMP-9 activity and potentially increase the risk of psychosis. Additionally, we explore the gene-environment interactions of four MMP-9 gene polymorphisms (rs3918242, rs17576, rs17577, and rs20544), examining how variations in these polymorphisms and their interaction with childhood/adolescent trauma may affect plasma MMP-9 activity and related molecules such as the inactive zymogen, proMMP-9, and tissue inhibitor of metalloproteinases-1 (TIMP-1), a potent endogenous inhibitor of MMP-9 activity. Participants were recruited from a case-control study conducted in the catchment area of Ribeirão Preto, Brazil. The study included 143 individuals experiencing FEP, 73 non-affected siblings, and 286 community-based matched for age and sex. Blood samples were collected for plasma analysis, with MMP-9 activity measured via gel zymography and TIMP-1 levels assessed using ELISA kits. We also evaluated gene-environment interactions by analyzing MMP-9 gene polymorphisms in a subsample of individuals and their associations with trauma and MMP-9 activity. As expected, a history of childhood trauma was significantly associated with FEP and conferred a threefold increase in relative risk. While MMP-9 polymorphisms were not directly associated with FEP, gene-environment interactions were observed between trauma and the rs20544, rs17576, and rs17577 polymorphisms, leading to increased pro-MMP-9 activity and a higher pro-MMP-9/TIMP-1 ratio. We did not find changes in plasma MMP-9 activity among the groups. However, higher pro-MMP-9 activity/TIMP-1 levels ratio in individuals exposed to childhood trauma, particularly among FEP patients, were found. Additionally, there was a significant interaction between childhood trauma and FEP status, with FEP patients exposed to trauma showing elevated MMP-9 and pro-MMP-9 activity , and their ratios to TIMP-1 levels. Our findings suggest that MMP-9 plays a role in the pathophysiology of psychosis, with childhood trauma influencing MMP-9 activity and potentially increasing the risk of psychosis. The interaction between MMP-9 gene polymorphisms and trauma further highlights the complex interplay between genetic and environmental factors in the development of psychotic disorders.